Does phenotyping of Hypericum secondary metabolism reveal a tolerance to biotic/abiotic stressors? - Bruňáková, Katarína; Bálintová, Miroslava; Petijová, Linda; Čellárová, Eva (Frontiers in Plant Science, 2022)
In this review we summarize the current knowledge about the changes in Hypericum secondary metabolism induced by biotic/abiotic stressors. It is known that the extreme environmental conditions activate signaling pathways leading to triggering of enzymatic and non-enzymatic defense systems, which stimulate production of secondary metabolites with antioxidant and protective effects. Due to several groups of bioactive compounds including naphthodianthrones, acylphloroglucinols, flavonoids, and phenylpropanes, the world-wide Hypericum perforatum represents a high-value medicinal crop of Hypericum genus, which belongs to the most diverse genera within flowering plants. The summary of the up-to-date knowledge reveals a relationship between the level of defense-related phenolic compounds and interspecific differences in the stress tolerance. The chlorogenic acid, and flavonoids, namely the amentoflavone, quercetin or kaempferol glycosides have been reported as the most defense-related metabolites associated with plant tolerance against stressful environment including temperature, light, and drought, in association with the biotic stimuli resulting from plant-microbe interactions. As an example, the species-specific cold-induced phenolics profiles of 10 Hypericum representatives of different provenances cultured in vitro are illustrated in the case-study. Principal component analysis revealed a relationship between the level of defense-related phenolic compounds and interspecific differences in the stress tolerance indicating a link between the provenance of Hypericum species and inherent mechanisms of cold tolerance. The underlying metabolome alterations along with the changes in the activities of ROS-scavenging enzymes, and non-enzymatic physiological markers are discussed. Given these data it can be anticipated that some Hypericum species native to divergent habitats, with interesting high-value secondary metabolite composition and predicted high tolerance to biotic/abiotic stresses would attract the attention as valuable sources of bioactive compounds for many medicinal purposes.